Proceedings of stakeholder' consultation meeting on agrifood value chains in Odisha: Challenges and Opportunities - Odisha University of Agriculture and Technology; International Food Policy Research Institute (Odisha University of Agriculture and Technology, 2024)
A stakeholders’ consultation meeting entitled “Agrifood Value Chains in Odisha Challenges and Opportunities” was organised by Agriculture Consultancy Support Service Cell (ACSSC), OUAT at Auditorium, Department of Agriculture and Farmers Empowerment (Krushi Bhawan), Bhubaneswar on 29th November 2023 as per the Term of Reference (ToR) of the consultative project “Drivers of agrifood systems growth in Odisha” funded by International Food Policy Research Institute (IFPRI). The meeting witnessed the participation of key stakeholders from both national and international organisations including Government officials, faculties and scientists of Universities and academic institutions, representatives from civil societies, agriculture marketing experts and private companies involve in agriculture value chain in Odisha. The objectives of the meeting were to identify the drivers of agrifood system (AFS) as well as the priority areas of the interventions, to analyze the emerging challenges and opportunities and to understand essential policy and institutional reforms for transforming farm and off farm sectors in Odisha. Besides the inaugural and the plenary session, there were three technical sessions designed to discuss and deliberate and gain consensus on the policy and institutional challenges facing the agrifood system and prioritize action points in Odisha. The thematic areas of discussion in the three sessions are the transformation of agrifood value chains in Odisha, transformation of horticulture value chains in Odisha and the transformation of fisheries and livestock value chains in Odisha.